1988
DOI: 10.1088/0268-1242/3/4/004
|View full text |Cite
|
Sign up to set email alerts
|

Electrical inhomogeneity in 1" diameter partially dislocation-free undoped LEC GaAs

Abstract: The influence of dislocations on the electrical properties of 1" partially dislocation-free LEC GaAs has been studied as a function of the fraction of melt solidified ( g ) . Microscopic electrical characterisation was performed using spreading resistance and anodisation imaging techniques, and Hall measurements at 294-400 K were employed for macroscopic characterisation.The zero-dislocation-density seed end regions are microscopically uniform with consistently high mobility, resistivity and thermal activation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

1990
1990
1999
1999

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…[1][2][3] The Hall mobility demonstrates, however, in all these crystals a pronounced minimum in the transition region from semi-insulating to medium resistivity. 1,2,5 This phenomenon observed generally in undoped bulk-grown GaAs is connected with the shift of the Fermi level from the EL2 to the next shallower defect level ͑e.g., off-center O As ). 3,5 Nevertheless, the physical mechanism, which causes such mobility minimum, is not investigated in detail.…”
Section: Enhancement Of the Hall Mobility In Undoped Gaas With Low Camentioning
confidence: 89%
See 1 more Smart Citation
“…[1][2][3] The Hall mobility demonstrates, however, in all these crystals a pronounced minimum in the transition region from semi-insulating to medium resistivity. 1,2,5 This phenomenon observed generally in undoped bulk-grown GaAs is connected with the shift of the Fermi level from the EL2 to the next shallower defect level ͑e.g., off-center O As ). 3,5 Nevertheless, the physical mechanism, which causes such mobility minimum, is not investigated in detail.…”
Section: Enhancement Of the Hall Mobility In Undoped Gaas With Low Camentioning
confidence: 89%
“…[1][2][3][4] The carrier concentration profile measured along the axis of such ingots usually shows a monotonic increase from semi-insulating to a high-resistivity or even low-resistivity tail end. [1][2][3] The Hall mobility demonstrates, however, in all these crystals a pronounced minimum in the transition region from semi-insulating to medium resistivity. 1,2,5 This phenomenon observed generally in undoped bulk-grown GaAs is connected with the shift of the Fermi level from the EL2 to the next shallower defect level ͑e.g., off-center O As ).…”
Section: Enhancement Of the Hall Mobility In Undoped Gaas With Low Camentioning
confidence: 99%
“…3,5 The most striking feature of the h (n) curves is a maximum at about nϭ3ϫ10 7 cm Ϫ3 followed by a strong decrease of H with increasing n. Whereas the data points of Nakamura et al 3 yielded a broad minimum extending up to 10 13 cm Ϫ3 , the present authors observed a second maximum of H at about nϭ3ϫ10 11 cm Ϫ3 causing a pronounced minimum at about 1ϫ10 10 cm Ϫ3 in all investigated crystals. Young et al 4 and Kaminaka et al 6 showed that a distinct correlation exists between the lowering of the Hall mobility and the microscopic nonuniformity of the resistivity. However, only in a few papers 4,7 were these electrical nonuniformities explicitly brought in connection with the cellular structure of dislocations, which is the main source of nonuniformities in undoped bulk-grown GaAs.…”
Section: Introductionmentioning
confidence: 99%
“…These cannot be explained by the usual scattering mechanisms but were attributed to nonuniformities in the samples. [1][2][3][4][5][6] A distinct correlation between the Hall mobility H and the carrier concentration n was found. 3,5 The most striking feature of the h (n) curves is a maximum at about nϭ3ϫ10 7 cm Ϫ3 followed by a strong decrease of H with increasing n. Whereas the data points of Nakamura et al 3 yielded a broad minimum extending up to 10 13 cm Ϫ3 , the present authors observed a second maximum of H at about nϭ3ϫ10 11 cm Ϫ3 causing a pronounced minimum at about 1ϫ10 10 cm Ϫ3 in all investigated crystals.…”
Section: Introductionmentioning
confidence: 99%
“…In ͑liquid encapsulated Czo-chralski͒ ͑LEC͒ GaAs with an epd ͑etch pit density͒ between 5ϫ10 4 and 1ϫ10 5 cm Ϫ2 , the dislocations are arranged in a cellular structure ͑with a cell diameter between 100 and 300 m͒ formed by dislocation-rich cell walls and nearly dislocation-free cell interiors. This cellular structure is reflected in the electrical properties as revealed by locally resolved resistivity measurements [1][2][3] showing cell wall regions with clearly lower resistivity than the cell interiors. The dislocation density of ͑vertical gradient freezing͒ ͑VGF͒ grown GaAs crystals is much lower (Ϸ10 3 cm Ϫ2 ) than in LEC GaAs and therefore the average diameter of the broken cells is much larger ͑1-2 mm͒.…”
Section: Introductionmentioning
confidence: 99%